PERANCANGAN TATA LETAK LABORATORIUM PAKAN DENGAN METODE COMPUTERIZED RELATIONSHIP LAYOUT PLANNING DI INDUSTRI PENGGEMUKAN SAPI - Dian Fajarika; Rinda Gusvita; Novicha Sofriani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Feed laboratory is a facility that guarantees feed quality in the feedlot industry. But the existence of this laboratory has not been fully considered both in terms of facilities and layout that ease the movement of workers. This research aims to analyze machine and raw material properties in the feed laboratory, to find total closeness rating between facilities according the need and designing the layout of facilities in the laboratory that can streamline the material flow. The problem is how to design facility layout in feed laboratory which has different tool and machine characteristics in limited space, how to plan material flow that can minimize work flow. The method used is computerized relationship layout planning (CORELAP). The result obtained is the design of the laboratory layout by comparing the optimum distance on the inter-work track. The calculation value from allocation relationship diagram showed the biggest total closseness rating is the testing room. From the calculation of the distance difference layout design, it is known that the second alternative provides a better solution with the largest distance difference of 41.52 for space with condition should be close and the distance difference of -31.21 for space with the condition should not be close. Keyword: feed laboratory layout, feedlot industry, computherized relationship layout planning